Stability improvement of multi-beam picosecond–petawatt laser system for ultrahigh peak-power applications - Tang, Shunxing; Guo, Yajing; Yang, Pengqian; Jiang, Xiuqing; Hua, Neng; Zong, Nan (Frontiers in Physics, 2023)
Pointing fluctuations of beams reduce the possibility of incoherent or coherent addition for ultrahigh peak power in a multi-beam picosecond–petawatt laser system. Pointing fluctuations on the target were observed on Shenguang Upgrade Petawatt (SGII-UP-Petawatt) beam using a high-speed and high-resolution active pointing stabilization control system. The maximum frequency of the pointing fluctuations was less than 50 Hz, and the amplitude was approximately 2.8 µrad (RMS). An online test of pointing fluctuations with active stabilization control demonstrated that pointing fluctuations could be reduced to 0.63 µrad (RMS), approximately one-quarter of that without active stabilization control. The benefits of reduced pointing fluctuation were estimated using a multi-beamlet petawatt laser system; the results demonstrated that peak power could be increased by 51.7% when active stabilization control was used in an eight-beamlet picosecond–petawatt laser system.